THEORETICAL BASES AND POSSIBILITIES OF FORENSIC MICROLOGY - Mirzoyan, Sergey (State and Law, 2020)
The given article aims to analyze the theoretical foundations and possibilities offorensic micrology and discuss the related issues.The article deals with forensic micrology development history, essence andsubject, forensic examination objects, its important role and significance in crimedetection, organizational and theoretical problems in forensic practice, as wellprospects for the development of forensic micrologyusing modern techniques.
Keywords: forensic techniques, forensic micrology, micro-objects, expert opinion, place of incident, forensic expertise